Reduction of stool bacterial counts and prevention of diarrhea using an oral homeopathic product in newborn lambs - Fortuoso B.F.* (2019)
© 2018 Elsevier Ltd Lamb farming is generally a secondary activity for farmers, and many breeding systems suffer from management failures that impair production. One reason for decline in performance is enteritis, usually affecting newborn lambs. Enteritis can be fatal, especially in dairy herds. Generally, lambs are fed sucrose or unprocessed milk from sheep or cow that is heated and fed to animals two or three times a day in baby bottles. However, on most farms, milk temperature differs among feeds, as often the process of alteration among diet adaptations is deficient, contributing to enteritis and consequent diarrhea. Therefore, the objective of the present study was to verify the administration of the homeopathic product (Dia 100 ® ) in newborn and bottle-fed lambs, in order to prevent or minimize the occurrence of diarrhea. We studied 60 lambs, divided into two groups with ten repetitions each (n = 30) and during the nursing period (1–45 days of life). Animals in the treated group received the homeopathic product (36 g) orally divided into three doses (1, 7 and 14 days of life). We measured weight gain, mortality, bacterial counts (Escherichia coli and total coliforms) in feces, hematological analysis (leukocytes, hematocrit, hemoglobin and erythrocytes) and biochemical analyses (glucose, triglycerides, cholesterol, albumin, globulin, urea and total protein) at four time-points. There were no differences in weight gain between groups (P > 0.05); however, there was a higher mortality rate in the control group (13%) than in the treated group (6%). E. coli counts were significantly higher in the stools of control group lambs on days 15 and 45 of the experiment (P < 0.05). Total leukocyte counts were greater in treated animals due to greater numbers of lymphocytes on day 15 of the experiment (P < 0.05). In the treated group, we found higher serum levels of total protein, urea (day 15), globulin and triglycerides (days 15 and 30). In the period of administration of the homeopathic product, there was substantial and significant reduction of cases of diarrhea (up to day 14); however, after this period, there were no difference between groups. Based on these results, we concluded that the homeopathic product had moderate efficacy in terms of control of diarrhea. The treated lambs made better use of nutrients, contributing to the development of their immune responses.